Performance of automated urine analyzers using flow cytometric and digital image-based technology in routine urinalysis. (3rd October 2019) - Kucukgergin, Canan; Ademoglu, Evin; Omer, Beyhan; Genc, Sema
Abstract: The purpose of this study was to evaluate the analytical performances of Sysmex UF-5000 and Dirui FUS-200 and to compare the results with manual microscopy and between each other. Two hundred fifty urine samples were analyzed for evaluation. Mid-stream specimens were studied sequentially using Dirui FUS-200 and Sysmex UF-5000, and also with manual microscopy within one hour. The physical and chemical components of urinalysis, and sediment results were investigated. The precision results of the FUS-200 and UF-5000 for WBCs, RBCs, and ECs were acceptable. The both analyzers demonstrated good linearity ( r > 0.97), with no carry-over. The comparisons of FUS-200 and UF-5000 with manual microscopy for RBCs, WBCs, and ECs on 250 samples exhibited good agreement with little bias ( R > 0.780). Only, the moderate agreements were obtained for calcium oxalate for both analyzers ( R = 0.512, and 0.648, respectively). The sensitivities of the FUS-200 and UF-5000 were 75.8% and 86.8%, with specificities of 92.3% and 87.8% for WBCs, for RBCs the sensitivities were 91.1%, and 84.4% with specificities of 82.2%, and 89.6% for both analyzers. Kappa values of the UF-5000 were higher than FUS-200 for WBCs, RBCs, ECs, and calcium oxalate. The FUS-200 and UF-5000 urine analyzers, are both accurate, very precise systems and can be safely used in clinical laboratories. However, due to the technological characteristics of the UF-5000 analyzer, its positive impacts on the morphologic recognition and enumeration of RBCs and WBCs should be taken into account, particularly in university hospital laboratories with high patient volumes.